2021
DOI: 10.3390/pharmaceutics13071079
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Nasal Aerosol Depositions: An Insight for Direct Nose to Brain Drug Delivery

Abstract: The nasal cavity is an attractive route for both local and systemic drug delivery and holds great potential for access to the brain via the olfactory region, an area where the blood–brain barrier (BBB) is effectively absent. However, the olfactory region is located at the roof of the nasal cavity and only represents ~5–7% of the epithelial surface area, presenting significant challenges for the deposition of drug molecules for nose to brain drug delivery (NTBDD). Aerosolized particles have the potential to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 120 publications
1
27
0
Order By: Relevance
“…Maaz et al also reported in vitro deposition of about 5% in the olfactory region for liquid sprays. Moreover, their simulations showed that the fraction of the formulation deposited in the olfactory region slightly decreases after the instillation, due to the movement of the liquid after impaction ( 15 ). On the other hand, the use of a dry powder seems to be a better choice for N2B delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Maaz et al also reported in vitro deposition of about 5% in the olfactory region for liquid sprays. Moreover, their simulations showed that the fraction of the formulation deposited in the olfactory region slightly decreases after the instillation, due to the movement of the liquid after impaction ( 15 ). On the other hand, the use of a dry powder seems to be a better choice for N2B delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Since the ultimate method to delivering NPs for nose-to-brain will be most likely through spray devices, the nasal deposition following spraying has been studied by different variables, including airflow rate. The association between the inspiratory airflow rate and aerosol deposition patterns in the nose has been considered for aerosol deposition in the olfactory region for nose-to-brain delivery, although there is much debate about it, with contrasting results depending on the used model [70]. Thus, all these parameters should be considered in the evaluation of possible resistances that NPs can meet in the process of nose-to-brain delivery of their payload.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal and oromucosal drug delivery is a contemporary field of research, mostly because of the multiple advantages they offer beyond their most commercial designation—to treat and/or protect the mucosa. The nasal route stands out as one of the most prospective sites for peptide and protein delivery [ 195 ], and direct brain drug delivery (via the olfactory bulb) [ 196 , 197 ]; the buccal route reveals opportunities for sustained drug delivery, and the sublingual route allows fast access to the systemic circulation [ 198 , 199 ]; both the nasal and the oromucosal routes are eligible for mucosal vaccination, for which target zones are the lymphoid regions (NALT and MALT, respectively) [ 65 , 200 , 201 , 202 , 203 ]. However, in the light of the current topic, the focus will be directed to nasal and oromucosal drug administration for local protection.…”
Section: The Nasal and Oromucosal Drug Deliverymentioning
confidence: 99%